ANALISIS PENGARUH KEHALUSAN ABU TERBANG (FLYASH) TERHADAP STABILITAS DAN KEPADATAN CAMPURAN BETON ASPAL (AC-WC) - Rosyad, Farlin (Jurusan Teknik Sipil & Perencanaan Fakultas Teknik Universitas Sriwijaya, 2017)
In this study, the use of fly ash material as substitution material of fine fraction on asphalt mixture of AC-WC Concrete to study Marshall and Durability. Concrete of bitumen is one of plywood type of pavement construction of pavement. In this study will focus on the extent of the effect of Ash ash Effect on Asphalt Concrete Mixture -WC tehadap Stability and density of the concrete mixture of asphalt. and in the end it is hoped that later fly ash of coal which used to be a waste material can be utilized as substitution material of fine fraction and alternative filler in road construction. The conclusion obtained from the analysis of the influence of fineness to the stability and density of AC-Wc asphalt concrete is as follows : Stability: Value stability of the mixture in the review of fineness variation tends to increase substitution of fly ash content variation occurs at the rate of 6% optimum zone 3 is equal to 1.435kg and at the level of 8% zone 3 decreased to 1.421kg.KepadatanNilai Density (Bulk density Standard) the mixture in review of the fineness variations tends to increase. variation of fly ash content substitution occurred optimum at 8% level of zone 3 that is equal to 2,421kg / cc. Some suggestions that can be submitted to improve the results performance of concrete asphalt mixture (AC-WC) using subtitution smoothness and fly ash content are: a) for subsequent research in order to analyze the optimum asphalt content to the optimum ash content as the greater the use of fly ash content, the Marshall parameter value tends to be less than optimal andb) It is advisable to combine other types of substitution materials with fly ash to obtain more economical results.